An Opposite-Bending-and-Extension Soft Robotic Manipulator for Delicate Grasping in Shallow Water - Gong, Zheyuan; Chen, Bohan; Liu, Jiaqi; Fang, Xi; Liu, Zemin; Wang, Tianmiao; Wen, Li (Frontiers in Robotics and AI, 2019)
Collecting seafood animals (such as sea cucumbers, sea echini, scallops, etc.) cultivated in shallow water (water depth: ~30m) is a profitable and an emerging field that requires robotics for replacing human divers. Soft robotics have several promising features (e.g., safe contact with the objects, lightweight, etc.) for performing such a task. In this paper, we implemented a soft manipulator with an opposite-bending-and-extension structure. A simple and rapid inverse kinematics method is proposed to control the spatial location and trajectory of the soft manipulator’s end effector. We introduced the actuation hardware of the prototype, and then characterized the trajectory and workspace. We found that the prototype can well track fundamental trajectories such as a line and an arc. Finally, we construct a small underwater robot and demonstrated that the soft manipulator successfully collected multiple irregular shaped seafood animals of different sizes and stiffness at the bottom of the natural oceanic environment (water depth: ~10m).